KONTRATYP CZYNNOŚCI OPERACYJNO-ROZPOZNAWCZYCH - Prusak, Feliks (Zeszyty Prawnicze, 2016)
JUSTIFICATION IN OPERATIONAL AND RECONNAISSANCE ACTIVITIES Summary The subject of this article is justification, the exception to the prohibition of committing an offence or crime, by an officer of a penal prosecution agency undertaking operational and reconnaissance activities to detect a crime and identify its perpetrator. The article describes the essence of the relevant legal structure, the legal factors determining it, and the context of the action the officer may take within the limits of his powers and official duties.